Gifts, Unwanted and Ungiven. Issue 2 (4th July 2022) - Wulff, Helena
SUMMARY: Against a backdrop of gift‐giving and reciprocity as keys in building and confirming social relationships in the field, this fictional narrative reveals a string of gift‐giving events that did not work out. This outcome is rarely reported on in anthropology, but here one gift was returned immediately, another promised but never produced. There is also the anti‐climactic nature of a parting gift when it is time for the fieldworker to exit the field. The setting is Dublin's literary world, and the fieldwork includes a number of appreciated gifts, though not always in the form of an equal exchange of objects. The occurrence of unwanted and ungiven gifts that recur through the narrative are thorny reminders of the fragility of friendship in the field. The characters in the narrative are composite except for cameo appearances of named writers.